Customized reconstruction of an extensive mandibular defect: A clinical report. - Fernandes, N; van den Heever, J; Hoek, K; Booysen, G (PubMed: Journal of Prosthetic Dentistry, 2016)
Myoepithelial carcinomas are rare malignant tumors arising from salivary glands. They most commonly involve the parotid and minor salivary glands but may also occur in the submandibular glands. These tumors can become extensive, causing bony expansion and destruction. A 31-year-old man with a large swelling on the left side of the face is presented. Histologic examination of an incisional biopsy confirmed a diagnosis of a myoepithelial carcinoma arising from the left submandibular salivary gland. After tumor resection, the patient's mandible was reconstructed with a customized mandibular framework produced by means of 3-dimensional (3D) laser sintering. This approach significantly reduced cost, advanced surgical procedures, and operating room time, which is of great benefit in a developing country like South Africa.
Published Article